The Effect of Project-Based Learning on Student Creativity in Physics Learning - Mariam Ulfa; Wahyudi Wahyudi; Gunawan Gunawan; I Wayan Gunada (Indonesian Publication Center, 2024)
This quasi-experimental study aimed to examine the effect of implementing Project-Based Learning (PjBL) on students' creativity in physics learning. The study was conducted on eleventh-grade students at SMAN 1 Kediri, using a control group pretest-posttest design. The sample was selected purposively, with class XI MIPA 2 as the experimental group (receiving PjBL) and class XI MIPA 3 as the control group (receiving conventional learning). The results showed an increase in creativity in both groups, but the increase in the experimental group was significantly higher than in the control group. The hypothesis testing results confirmed that the PjBL model positively affects students' creativity in physics learning.